Nahdlatul Ulama's Ideological Hegemony in Nadirsyah Hosen's Oration: A Critical Discourse Analysis - Rahmania, Sofi Aulia (Universitas Dian Nuswantoro, 2022)
As a multicultural country, Indonesia has big challenges to maintain the harmony and unity. Nowadays, intolerance and acute extremism are rampant that spread to a group of people. These problems could disrupt national stability and inter-religious harmonies. To prevent divisions and wars between religious believers, the Ministry of Religion is aggressively promoting religious moderation in every line of society. The religious moderation was often conveyed by religious leaders, government, and leaders of sciences. The focus of this research is the ideological hegemony of Islam Nusantara in the speech which is delivered by Dr. KH. Nadirsyah Hosen, LL.M, MA., Ph.D (Gus Nadir). The data are fragments of the oration discourse that represent the hegemony of Islam Nusantara, while the data source used is a scientific oration discourse delivered by Nadirsyah Hosen at the 2nd Annual Conference for Moslem. Meanwhile, the data analysis method used Norman Fairclouh's Critical Discourse Analysis model, the first stage was description. Based on the results of the analysis, it was found that Gus Nadir represented the Islam Nusantara (Islamic archipelago's ideologies) in scientific orations with the theme of religious moderation through classification, rewording, overwording, and metaphors.